2001
DOI: 10.1300/j123v40n01_08
|View full text |Cite
|
Sign up to set email alerts
|

“La Jolla Confidential”

Abstract: SUMMARY. This paper describes a unique electronic journal publishing project involving the University of Kansas, the Big 12 Plus Libraries Consortium, the American Institute of Biological Sciences, Allen Press, and SPARC, the Scholarly Publishing and Academic Resources Coalition. This partnership is creating BioOnet, a database of over 30 full-text society journals in the biological and environmental sciences. The genesis and development of the project are described, and financial, technical, and intellectual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research for this article revealed that the Library Cooperative, while innovative, is not unique. For an example of a similar project model see Alexander and Goodyear (2001).…”
Section: Commitment From Diverse Partnersmentioning
confidence: 99%
“…Research for this article revealed that the Library Cooperative, while innovative, is not unique. For an example of a similar project model see Alexander and Goodyear (2001).…”
Section: Commitment From Diverse Partnersmentioning
confidence: 99%